Hydroponic on rock melon using deep flow technique (dft) system - Anis Izz Zayani, Ariffin Kamal (2025)
This study explores the feasibility and effectiveness of hydroponic systems for rock melon (Cucumis melo) cultivation in Malaysia, addressing limitations of traditional farming. Key water quality metrics were maintained within optimal ranges, with pH levels consistently between 5.5 and 6.5 and electrical conductivity (EC) at 1.2 mS/cm and oxidation-reduction potential (ORP) averaging +200 mV, promoting healthy nutrient uptake. The methodology involved implementing the DFT hydroponic system, where rock melon seeds were initially germinated in two methods, which by using ½ MS medium in conical flasks, and by using rock wool as a substrate before transferring into hydroponic system with regular monitoring of growth and water quality parameters. Using a Deep Flow Technique (DFT), this research optimized growth parameters and developed a tailored nutrient solution, resulting in a germination rate of 85% and a significant increase in biomass after two weeks. Over the course of six weeks, plant height increased steadily, reaching an impressive 60 cm by week six, demonstrating the efficacy of the hydroponic approach. The pruning of older leaves was conducted to promote airflow and encourage the growth of new leaves, which contributed to overall plant health. Chlorophyll content analysis indicated robust photosynthetic activity, with levels averaging 3.5 mg/g in hydroponically grown plants compared to 2.1 mg/g in traditionally grown counterparts. The findings suggest that hydroponics can enhance fruit quality and yield while mitigating environmental challenges, positioning it as a sustainable alternative for rock melon production in Malaysia. The AB mix solution used in this study provided essential macro and micronutrients for optimal plant growth, consisting of two components; A and B that were mixed in water to create a complete nutrient solution. In conclusion, this research underscored the potential of hydroponics as a sustainable agricultural practice in Malaysia, advocating for broader adoption of hydroponic techniques to ensure food security and meet consumer demands for high-quality produce while addressing sustainability concerns in agriculture.